PERLINDUNGAN HUKUM BAGI PEMEGANG HAK GADAI BERDASARKAN HUKUM ADAT TOLAKI DI KECAMATAN WAWOTOBI KABUPATEN KONAWE - Ni Nyoman Triana Suskendariani; Karmila Karmila (Lakidende Law Review, 2022)
Legal certainty of a land pawn agreement carried out using customary law in the Tolaki community is guaranteed by the customary law concerned because the dispute resolution that occurs is also resolved through a customary court, and the existence of the decision of the customary court that binds the disputing parties in addition to the application of strict sanctions in dispute resolution. In addition, the existence and existence of customary law is also supported by the provisions of the applicable legislation, which can be seen in Law Number 4 of 2004 concerning The provisions of the Basic Provisions of Judicial Power, in Article 28 paragraph (1) which states "Judges are obliged to explore, follow, and understand legal values ​​and a sense of justice that live in society". The decision issued by the court in case Number: 13/Pdt.G/2013/PN.Unh did not take into account the decision of the customary court on the grounds that the case would be processed in accordance with the applicable positive law and no attempt was made by the plaintiff to withdraw his lawsuit even though a customary trial has been carried out and the customary court has issued its decision.